Patologia em revestimentos cerâmicos de fachadas de edifícios: estudo regionalizado para a cidade de Divinópolis-MG - Leonardo Bento Ferreira de Toledo (2007)
The main objective of this study is to evaluate the pathologies in facades whit ceramic veneer. This work was developed in the city of Divinópolis - Minas Gerais, in different buildings that presented pathologies, and it's a quantitative study. The necessity of the study is to measure the pathologies in percents and identify the root of the problem. The authors concluded that a revision of the technical procedures applied on the construction of the buildings is necessary. The use of ceramic veneer is usual, but there are still many errors. In this article the term RFC means facades with ceramic veneer. It was verified that the pathologies mainly are located between the ceramic veneer and mortar. And too that the pathologies's distribution is near a GLAUSS's Normal curve.